NUTRIENT UTILISATION AND GROWTH OF CATFISH (CLARIASGARIEPINUSBURCHELL)FED GRADED LEVELS OF DIFFERENTLYPROCESSED SUNFLOWER (HELIANTHUS ANNUUSLINNAEUS) SEED MEAL (2014)
Increasing cost of feedstuffs due to competition among fish and other livestock feed industries necessitated research into Low-Cost Unconventional Feedstuffs (LCUF) for profitable fish production. The potential of sunflower (Helianthus annuus) seed as a LCUF has not been fully documented. The nutritional potentials of sunflower seed meal as a substitute for soybean meal in the diets of African catfish, Clarias gariepinus, were therefore investigated. Proximate and mineral composition of Boiled Sunflower Seed Meal (BSSM), Roasted Sunflower Seed Meal (RSSM), Mechanically Extracted Sunflower Seed Meal (MESSM) and Solvent Extracted Sunflower Seed Meal (SESSM) were determined using standard procedures. Nutrient digestibility of the meals was conducted in a feeding trial with C. gariepinus juveniles. The meals with best digestibility indices were each used for growth and nutrient utilisation studies. The BSSM and MESSM were each used to replace soybean meal at 0, 20, 40, 60, 80 and 100% respectively in formulating isonitrogenous (40% crude protein) and isocaloric (4651.5Kcal/kg) diets representing six treatments per meal. Diets were fed twice daily at 5% body weight to C. gariepinus juveniles (mean weight 21.3 0.1g) for 105 days. Mean Weight Gain (MWG), Specific Growth Rate (SGR) and Feed Conversion Ratio (FCR) were measured. Packed Cell Volume (PCV), White Blood Cells (WBC), Red Blood Cells (RBC), Plasma Glucose, Plasma Protein and Albumin were determined using standard procedures. Histo-pathological evaluations of the experimental fish were carried out. Data were analysed using descriptive statistics and ANOVA at p = 0.05. Crude protein (45.3%) was highest in SESSM and lowest (32.0%) in BSSM. Crude lipid (21.6%) and ash (5.1%) were highest in BSSM. Crude fibre varied from 14.2% in BSSM to 23.9% in RSSM. Calcium (0.4 mg/g), phosphorus (1.7 mg/g) and iron (0.4 g/g) were highest in BSSM. Tannin ranged from 0.2 g/g in RSSM to 0.4 g/g in both SESSM and MESSM. Oxalate varied from 0.1g/g in BSSM to 0.2 g/g in MESSM. Apparent digestibilities of dry matter (84.3%) and crude protein (85.9%) were highest in fish fed MESSM and least (82.0% and 80.7%) in fish fed RSSM respectively. Fish fed 20% BSSM-based diet had significantly higher MWG (52.5 2.5g), SGR (0.5%) and least FCR (0.6). Fish fed 20% MESSM inclusion had the highest PCV (38.0%) and RBC (10.2 0.1 x 1012/mL). Elevated WBC value (12.5 x109/mL) was obtained in fish fed 80% MESSM. Fish fed 40% MESSM had the highest total plasma protein (4.2 0.1 g/100mL) while a depressed level (2.3 0.0 g/100mL) was obtained at 100% BSSM inclusion. Albumin was highest (1.4 0.1 g/100mL) in fish fed 80% MESSM and least (0.9 0.1 g/100mL) at 100% BSSM inclusion. Fish fed BSSM and MESSM at inclusion levels above 20% had significant increase in plasma glucose level. Diffuse vacuolations and vacuolar degeneration of liver hepatocytes, as well as tubular epithelial degeneration of the kidney were observed for BSSM and MESSM inclusion levels above 20%. Substitution of 20% boiled sunflower seed meal for soybean meal in the diet enhanced optimal nutrient utilisation and growth in Clarias gariepinusjuveniles. Inclusion above this level caused nutritional and health hazards to the fish.